SKALA KECIL, IDEA BESAR: KRITIKAN NARATIF TERHADAP KARYA-KARYA TEATER ALTERNATIF DI STOR TEATER DBP: SMALL SCALE, BIG IDEAS: NARRATIVE CRITICISM OF ALTERNATIVE THEATRES IN STOR TEATER DBP - Musa, Syahrul Fithri; Samsuddin, Mohd Effindi (Jurnal Pengajian Melayu (JOMAS), 2020)
This paper aimed to discuss chosen alternative theatre writings which had been staged at Stor Teater Dewan Bahasa dan Pustaka (DBP) from 2003 to 2013. The chosen shows were picked from a pool of various works done by playwright-directors of different age groups, educational backgrounds and experiences in theatre such as Dinsman, Nam Ron, A. Wahab Hamzah, Fasyali Fadzly and Aloy Paradoks. A narrative criticism analysis was then made upon five informants who were also playwrights and directors of ten shows presented at the Stor Teater DBP, Kuala Lumpur, throughout 11 years from 2003 to 2014. The analysis was made to understand their preferences and approaches to writing. This paper highlighted aspects of their writings, for example, idea, process and space, to retrieve early evidence of the concept ‘small scale, big ideas’ within alternative Malay theatre. Results showed two approaches that have been utilised – writing based on a prior full narrative or a performance concept – thereby showing an understanding of distinct creative processes. This phenomenon is related to the ideologies held by each of the playwright-director studied. Keywords: Theatre, narrative criticism, scriptwriting Malay alternative theatre, performing arts.